2007
DOI: 10.1002/anie.200704484
|View full text |Cite
|
Sign up to set email alerts
|

Are Environmentally Coupled Enzymatic Hydrogen Tunneling Reactions Influenced by Changes in Solution Viscosity?

Abstract: The role and importance of protein dynamics in enzymatic reactions remains a key question in enzymology. [1][2][3][4][5] Of great current interest is whether enzymes have evolved to use quantum tunneling to the best advantage by, when necessary, coupling specific protein motions (vibrations) to the tunneling reaction coordinate. It is now widely accepted that H tunneling (proton, hydrogen, or hydride) occurs in enzymecatalyzed reactions, [1,[6][7][8][9][10][11] but the role of promoting motions in modulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…First, we re-analyze the dependence of k obs on glycerol concentration (data taken from ref. [27]) in terms of the solvent dielectric. 2 Additionally, we also measure the rate of the RHR of MR in 10 % and 20 % v/v ethanol.…”
Section: Solvent Dielectricmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we re-analyze the dependence of k obs on glycerol concentration (data taken from ref. [27]) in terms of the solvent dielectric. 2 Additionally, we also measure the rate of the RHR of MR in 10 % and 20 % v/v ethanol.…”
Section: Solvent Dielectricmentioning
confidence: 99%
“…In combination, this has led us to describe the hydride transfer (denoted H-transfer) within the context of modern environmentally coupled models of H-tunnelling, [19][20][21]26] such that the enzyme requires a promoting motion to move the nicotinamide C4ÀH sufficiently close to the FMN N5 atom to facilitate H-transfer by tunnelling. Recently, we have shown that the rate of the H-transfer reaction in MR is insensitive to changes in solution viscosity, [27] suggesting that this putative promoting motion, like that for aromatic amine dehydrogenase, [11,28] may be localized at the active site of the enzyme (c.f. the case argued for long-range coupled motions in for example, alcohol dehydrogenase, [29,30] The reductive half-reaction of morphinone reductase involves a hydride transfer from enzyme-bound b-nicotinamide adenine dinucleotide (NADH) to a flavin mononucleotide (FMN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For studies of the temperature dependence of rate constants, data were fitted to the Eyring equation. For viscosity studies, glycerol solutions were prepared by weight and calculation of solution viscosity was as described (24). The effect of viscosity on the observed rate was fitted to Equation 1 (25,26) to describe the contribution of the protein friction to the total friction of the system,…”
Section: Methodsmentioning
confidence: 99%
“…Significant changes in the magnitude of an enzymatic KIE through, e.g., environmental perturbations (Hay et al , 2008b or mutagenesis (Pudney et al 2007) will generally occur, in part or wholly, due to structural perturbation of the active site. Care must then be taken when interpreting such data.…”
Section: Experimental Evidence For H-tunneling In Enzymesmentioning
confidence: 99%